Estimating Who Benefits from Productivity Growth: Direct and Indirect Effects of City Manufacturing TFP Growth on Wages, Rents, and Inequality - Richard Hornbeck; Enrico Moretti (Institute of Labor Economics (IZA), 2019)
We estimate direct and indirect effects of total factor productivity growth in manufacturing on US workers' earnings, housing costs, and purchasing power. Drawing on four alternative instrumental variables, we consistently find that when a city experiences productivity gains in manufacturing, there are substantial local increases in employment and average earnings. For renters, increased earnings are largely offset by increased cost of living; for homeowners, the benefits are substantial. Strikingly, local productivity growth in manufacturing reduces local inequality, as it raises earnings of local less-skilled workers more than the earnings of local more-skilled workers. This is due, in part, to lower geographic mobility of less-skilled workers. However, local productivity growth also has important indirect effects through worker mobility. We estimate that 38% of the overall increase in workers' purchasing power occurs outside cities directly affected by local TFP growth. The indirect effects on worker earnings are substantially greater for more-skilled workers, due to greater geographic mobility of more-skilled workers, which increases inequality in other cities. Neglecting these indirect effects would both understate the overall magnitude of benefits from productivity growth and misstate their distributional consequences. Overall, US workers benefit substantially from manufacturing productivity growth. Summing direct and indirect effects, we find that manufacturing TFP growth from 1980 to 1990 increased purchasing power for the average US worker by 0.5-0.6% per year from 1980 to 2000. These gains do not depend on a worker's education; rather, the benefits from productivity growth mainly depend on where workers live.
Keywords: J20; 330; local labor markets